Pagan philosophers in late antique society : with special reference to Iamblichus and his followers - Fowden, G (1979)
The purpose of this study is to examine, from an historical point of view, the character of pagan philosophical life in late antiquity (A.D. 200-400). The primary vocation of the philosopher is in all ages the cultivation and propagation of wisdom; and in the eyes of contemporaries and posterity alike, his reputation rests upon his teaching, whether oral or committed to writing. His personal circumstances and actions are of secondary interest. Yet philosophers have been known to stir revolutions through their words; and any man who teaches plays a part, however minute, in the shaping of society. The study of the lives of philosophers, in other words, is a legitimate part of the historian's concern - and of the philosopher's too, in so far as a teacher illustrates his doctrines in the conduct of his own affairs. Continued in thesis ...